PENGARUH PEMUPUKAN KALIUM TERHADAP PERKEMBANGAN POPULASI KUTU DAUN (Aphis glycines Matsumura) DAN HASIL KEDELAI - Hendrival Hendrival; Latifah Latifah; Idawati Idawati (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2014)
The research was aimed at studying effects of potassium on the development of Aphis glycines populations and soybean yield. The experiment was conducted in Village Rayeuk Naleung, Sub district Tanah Luas, District North Aceh from July to September 2013. The experiment was arranged in a randomized complete block design (RCBD) with 3 replicates. The treatment was without fertilizer, potassium fertilizer at a dose of 25 kg/ha K2O, 50 kg K2O/ha and 75 kg K2O/ha. The variables observed were populations of A. glycines and components of yield soybean. The results showed that potassium at doses of 75 kg K2O/ha can reduce populations of A. glycines and soybean yield increase as compared to potassium fertilization at a dose of 25 kg/ha K2O and 50 kg K2O/ha.